2011
DOI: 10.1007/s00432-011-1078-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of coagulation factors and their receptors in tumor tissue and coagulation factor upregulation in peripheral blood of patients with cerebral carcinoma metastases

Abstract: These observations support the hypothesis of a link between the hemostatic system in the periphery and the malignant tumor disease even when the tumor is an intracerebral metastasis and the affected patient currently is free of a systemically active tumor. The results of this study support the hypothesis that the concerted action of coagulation factors and their receptors within the metastasis tissue itself and the systemic coagulation system could control the malignant behavior of tumor disease and make large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…reported that PAR‐4 protein was overexpressed in the majority of stage IB NSCLC tissues (65% of all cases and 87% of adenocarcinoma cases) and overexpression of PAR‐4 was associated with significantly shorter 3‐year survival . PAR‐4 expression was also detected in intracerebral metastases of small cell lung carcinoma in a recent study . However, Jiang et al .…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…reported that PAR‐4 protein was overexpressed in the majority of stage IB NSCLC tissues (65% of all cases and 87% of adenocarcinoma cases) and overexpression of PAR‐4 was associated with significantly shorter 3‐year survival . PAR‐4 expression was also detected in intracerebral metastases of small cell lung carcinoma in a recent study . However, Jiang et al .…”
Section: Discussionmentioning
confidence: 90%
“…The F2RL3 gene codes for the thrombin PAR‐4, which is expressed in a number of human tissues, including blood leukocytes and lung tissue . The function of PAR‐4 is not fully clear yet but there is emerging evidence that it might be involved in the pathophysiology of several malignant tumors and metastasis, including lung cancer . Ghio et al .…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, coagulation factors were found to be expressed in brain metastases of human clear cell renal cancer and small cell lung carcinoma. 138 TFPI was found to be elevated in plasma of patients with several PBTs and SBTs, and further studies of a possible link between coagulopathy and brain metastasis would be of great interest.…”
Section: Coagulation System and The Natural History Of Brain Tumorsmentioning
confidence: 94%
“…92,100 TF upregulation was also observed in the case of ligand dependent activation of the MET receptor in MB cells (DAOY), 97 and these properties were mitigated by the expression of the oncogenic miR-520 g. 137 Although TF is among the most frequently studied molecular paradigms of procoagulant conversion in cancer, the expression of other coagulation factors has also been reported in various tumor types, including FVII, 124 prothrombin, 125,126 FX, PAR-1, and other factors. 128,138 This is of note as some of these proteins are normally produced exclusively in the liver and under control of vitamin K-dependent mechanisms, which is the principle behind using vitamin K antagonists (warfarin) to control cancer coagulopathy. 139 To examine whether the ectopic (extrahepatic) production of coagulation factors could be a result of oncogenic transformation, two human glioma cell lines (U87 and U373) were engineered to express mutant EGFRvIII and tested for levels of elements of the TF-related coagulation pathway at both messenger RNA (mRNA) and protein levels.…”
Section: Genetic Determinants Of Brain Tumor Coagulomementioning
confidence: 99%
“…The drugs used in this study were RS67333, a potent and highly selective 5-HT4 partial agonist [10], and RS23597, a high affinity and selective competitive antagonist at 5-HT4 receptors [40], from (TOCRIS bioscience. USA) and MK801 (NMDA receptor antagonist, Sigma, Poole, Dorset, UK).…”
Section: Drugsmentioning
confidence: 99%